Mouse Dendritic Cells Pulsed with Capsular Polysaccharide Induce Resistance to Lethal Pneumococcal Challenge: Roles of T Cells and B Cells - Cohen, Noam; Margalit, Raanan; Pevsner-Fischer, Meirav; Yona, Simon; Jung, Steffen; Eisenbach, Lea; Cohen, Irun R. (PLOS ONE, 2012)
Mice are exceedingly sensitive to intra-peritoneal (IP) challenge with some virulent pneumococci (LD50 = 1 bacterium). To investigate how peripheral contact with bacterial capsular polysaccharide (PS) antigen can induce resistance, we pulsed bone marrow dendritic cells (BMDC) of C57BL/6 mice with type 4 or type 3 PS, injected the BMDC intra-foot pad (IFP) and challenged the mice IP with supra-lethal doses of pneumococci. We examined the responses of T cells and B cells in the draining popliteal lymph node and measured the effects on the bacteria in the peritoneum and blood. We now report that: 1) The PS co-localized with MHC molecules on the BMDC surface; 2) PS-specific T and B cell proliferation and IFNγ secretion was detected in the draining popliteal lymph nodes on day 4; 3) Type-specific resistance to lethal IP challenge was manifested only after day 5; 4) Type-specific IgM and IgG antibodies were detected in the sera of only some of the mice, but B cells were essential for resistance; 5) Control mice vaccinated with a single injection of soluble PS did not develop a response in the draining popliteal lymph node and were not protected; 6) Mice injected with unpulsed BMDC also did not resist challenge: In unprotected mice, pneumococci entered the blood shortly after IP inoculation and multiplied exponentially in both blood and peritoneum killing the mice within 20 hours. Mice vaccinated with PS-pulsed BMDC trapped the bacteria in the peritoneum. The trapped bacteria proliferated exponentially IP, but died suddenly at 18–20 hours. Thus, a single injection of PS antigen associated with intact BMDC is a more effective vaccine than the soluble PS alone. This model system provides a platform for studying novel aspects of PS-targeted vaccination.